EMOTION REGULATION DIFFICULTIES IN DEPRESSION - Paiča, Inese; Mārtinsone, Kristīne; Taube, Māris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Patients diagnosed with depression often experience difficulty in regulating their emotions due to non-adaptive regulatory strategies (e.g., avoidance, suppression, rumination). Adaptive emotion regulation skills (e.g., awareness, acceptance, self-support) can be trained and improved through psychological treatment. The objective of this study was to identify differences in emotion regulation skills between a clinical group of patients with depression (n=56) and a non-clinical group (n=56), adults without symptoms of depression. Methods. The study was based on socio-demographic survey and three self-report questionnaires adapted for use in Latvia: Difficulties in Emotion Regulation Scale (DERS; Gratz & Roemer, 2004), Emotion Regulation Skills Questionnaire (ERSQ; Berking & Znoj, 2008) and Emotion Regulation Questionnaire (ERQ; Gross & John, 2003). Results. Compared to the non-clinical group, the clinical group presented significantly decreased scores in several scales of ERSQ: Understanding, Self-support, Tolerance, Acceptance, Modification (p<.001) and increased scores in four scales of DERS: Lack of emotional clarity, Difficulty engaging in goal-directed behaviour, Non-acceptance of emotional responses and Limited access to effective emotion regulation strategies (p<.001). Conclusions. This study helps to identify the main emotion regulation difficulties for depression patients in Latvia – the ability to understand, accept, tolerate and modify emotions.